PRO ENVIRONMENTAL BEHAVIOR OF TRAVELLERS ON CITY SITES IN DENPASAR CITY - Gde Bagus Brahma Putra; Made Santana Putra Adiyadnya; Ni Putu Yuria Mendra (AIBPM Publisher, 2019)
Pro-environmental behavior is needed to overcome complex problems in economic development. The tourism sector is one of the sectors supporting the regional economy. The attraction that is highlighted by the City of Denpasar is a historical heritage site. The behavior of tourists will greatly influence the existence of the site. This study aims to investigate whether energy conservation, mobility and transportation, waste avoidance, recycling, consumerism, and vicarious behaviors toward conservation play a role in the formation of pro-environmental behavior among tourists visiting sites in the city of Denpasar.